Speed control of a wind turbine–driven doubly fed induction generator using sliding mode technique with practical finite‐time stability - Ali, Mohammad; Amrr, Syed Muhammad; Khalid, Muhammad (Frontiers in Energy Research, 2022)
This work investigates the application of sliding mode control (SMC) on a doubly fed induction generator (DFIG). In conventional control schemes like PI controllers, the responses are relatively slow, and the transient state is often subjected to sustained oscillation. Further, the PI control achieves lesser invariance behavior against system uncertainties, and the selection of its gain parameters is a skillful task. In contrast, the SMC is well-known for its faster convergence, robustness, and better transient and steady-state behavior. In this study, the nonsingular fast terminal sliding mode control (NSFTSMC) is applied in the speed loop of the rotor side vector control of DFIG. The proposed NSFTSMC scheme results in less speed fluctuation with a change in wind speed, which is maintained by controlling the torque component of the current (iq*). This paper also presents detailed modeling of the DFIG, power converters, and the related control schemes. Moreover, stability analysis of the proposed methodology ensures the practical finite time stability of the overall system. The comparative controller performance and validation are carried out in Matlab/Simulink environment. The proposed control strategy presents much better results than conventional PI-based control.